Vudcovstvi v spolecnosti 21. stoleti [Leadership in the 21st Century Society] - Zaušková, Anna and Pitra, Zbynek (Communication Today, 2013)
Each time brings changes in conditions that maintain the stability of social development. The role of the leaders of the society is to respond appropriately to these changes by changing the rules governing its functioning. In the case of large qualitative changes - and just such that are characteristic for the beginning of the 21st century - it means a radical change in society life. It is the task of leadership in the first century of the third millennium. Leadership skills of managers are essential for successful long-term development and of the organization social action (its business) and its long-term prosperity. The paper considers the synergy of management, and leadership, we also present new perspectives on the concept and role of leadership in business entities.
https://katalog.adlr.link/Record/ai-53-237653